Improvement of Teachers’ Ability to Carry on Positive Expectation Towards Students - Panjaitan, Lena N.; Joni, T. Raka; Handarini, Dhani; Kaluge, Laurens (Faculty of Psychology, Universitas Surabaya, 2011)
In the learning process at the classroom, the teachers’ teaching practice contributes significantly to the students’ academic achievement. One of the aspects of teaching practice, teachers’ positive expectation towards students, has been proved to play important roles in improving students’ academic performance. However, in fact, many students especially low achieving students believed that they were not treated accordingly. This study was conducted with the following purposes: (1) to improve the teachers’ positive expectations towards their students, especially low academic achieving students, and (2) to prosper the positive perception of students regarding their relationships with their teachers, classroom climate, and their academic ability. This study was designed as an action research. Although the results could only be observed in improving the classroom climate, and not yet on the understanding learning materials and improving thinking skills, but implementation of the program on a longer-term and more intensive feedback sessions could bring more valuable results regarding teaching effectiveness. Dalam proses pembelajaran di kelas, cara guru memandu pembelajaran akan memengaruhi keberhasilan dalam belajar. Salah satu aspek yang memengaruhi belajar siswa adalah harapan guru terhadapnya. Akan tetapi dari survei awal diperoleh bahwa para siswa, khususnya siswa dengan prestasi kurang, menilai guru kurang memberikan harapan positif terhadapnya. Penelitian ini bertujuan untuk 1) meningkatkan harapan guru terhadap siswa khususnya siswa dengan prestasi kurang dan 2) mengembangkan persepsi yang positif pada diri siswa terkait dengan relasinya dengan guru, iklim kelas, serta terhadap kemampuan belajarnya.Desain penelitian adalah penelitian tindakan, yang menghasilkan semakin positifnya persepsi siswa terhadap relasinya dengan guru serta iklim kelasnya setelah penerapan tindakan. Akan tetapi peningkatan pada persepsi terhadap kemampuan belajar serta prestasi akademik masih belum tampak. Penerapan tindakan yang berulang serta penyampaian balikan terhadap guru, diharapkan akan menghasilkan cara pembelajaran yang lebih efektif.